Rural telephony: Using BGAN to talk - Swanson, Gregg (Technical Centre for Agricultural and Rural Cooperation, 2008)
Using a VoIP conference call feature on a portable satellite connection, remote communities can express their opinions in their own language, and organizations can reduce travel costs